Qirâ’ah al-Kutub: Kajian Teoretis Berbasis Semantik Kontekstual pada Mahasiswa Studi Keislaman - Rosyidah, Inayatur; Mohamad Rofik Fitrotulloh (Jurnal Keislaman, 2025)
This study examines Qirâ’ah al-Kutub learning for Islamic studies students using a contextual semantic theory approach, aimed at enhancing the deep understanding of classical texts. The focus of this research is the analysis of Fath al-Qarib by Shaykh Muhammad bin Qasim Al-Ghaziy, particularly on the theme of al-Zawâj (marriage). The contextual semantic approach emphasizes the importance of language, situational, emotional, and cultural contexts in interpreting mufradât and sentence structures, ensuring students’ understanding is not merely lexical but holistic. This research employs a qualitative-theoretical method, involving literature studies of classical texts and scholarly references on contextual semantics and Qirâ’ah al-Kutub learning. The results indicate that the application of contextual semantic theory facilitates students in identifying key mufradât, understanding variations in word meanings, and relating classical texts to Islamic family law practices. The study also demonstrates that contextual approaches strengthen students’ analytical, interpretive, and critical reflection skills. These findings confirm that integrating contextual semantic theory in Qirâ’ah al-Kutub learning is an effective strategy for developing comprehensive classical text comprehension skills and serves as a crucial foundation for advancing Arabic language instruction and Islamic studies.